The Implementation MuluMile’s Social Activities Program “I Want to Be” in creating Community Development - Mubarok, Muhammad Luthfi; Koeswandi, Tika Annisa Lestari; Nurfitriya, Mira (A Social Science and Entrepreneurship Journal, 2021)
The purpose of this research is to explain the implementation MuluMile’s social activities program “I want to be” in creating community development. Development is an issue that is often an important discussion in efforts to increase and equalize the economy. Every element of society should take its role in realizing this, including MuluMile. Therefore, the "I Want to Be" program was created as a form of MuluMile's social responsibility towards the surrounding environment. This research uses descriptive-qualitative analysis method. This study concludes that our society should have the same opportunities and opportunities in improving its economy. Especially in realizing the desired profession/job. With the "I Want to Be" program from MuluMile, it is hoped that it will be able to break the gap/distance that is often an obstacle for people who live in areas/rural areas with limited information and infrastructure and make MuluMile as an Integrated Social Enterprise.